Determinants of the activity and substrate recognition of breast cancer resistance protein (ABCG2). (November 2014) - Szafraniec, Milena Julia; Szczygieł, Małgorzata; Urbanska, Krystyna; Fiedor, Leszek
Abstract The xenobiotic transporters are among the most important constituents of detoxification system in living organisms. Breast cancer resistance protein (BCRP/ABCG2) is one of the major transporters involved in the efflux of xenobiotics. To understand its role in chemotherapeutic and multidrug resistance, it is crucial to establish the determinants of its substrate specificity, which obviously is of high relevance for successful therapy of many diseases. This article summarizes the current knowledge about the substrate preferences of BCRP. We overview the factors which determine its activity, inhibition and substrate recognition, focusing on the structural features of the transporter. BCRP substrate specificity is quite low as it interacts with a spectrum of substances with only a few common features: hydrophobic and aromatic regions, possibly a flat conformation and the metal ion-, oxygen- and nitrogen-containing functionalities, most of which may be the donors/acceptors of H-bonds. Several amino acid residues and structural motifs are responsible for BCRP activity and substrate recognition. Thus, the active form of BCRP, at least a dimer or a larger oligomer is maintained by intramolecular disulfide bridge that involves Cys603 residues. The GXXXG motif in transmembrane helix 1, Cys residues, Arg482 and Lys86 are responsible for maintaining the protein structure, which confers transport activity, and the His457 or Arg456 residues are directly involved in substrate binding. Arg482 does not directly bind substrates, but electrostatically interacts with charged molecules, which initiates the conformational changes that transmit the signal from the transmembrane regions to the ABC domain.